Factors That Assosiated to Completed Doses of Immunization During Polio Supplementary Immunization Activities (SIA) in Mimika District 2024 - Muh. Afdhal (Science Tech Group, 2025)
In 2024, circulating vaccine-derived poliovirus type 2 (cVDPV2) was detected in Indonesia. In response, the Government of Indonesia declared a polio outbreak and launched a Polio Supplementary Immunization Activity (SIA) providing two doses of the Novel Oral Polio Vaccine type 2 (nOPV2) to children aged 0–7 years. This study aimed to identify factors associated with completion of the required nOPV2 doses during the Polio SIA in Mimika District, Central Papua Province. An analytic observational study with a cross-sectional design was conducted among children aged 0–7 years. A total of 356 respondents representing 776 eligible children were selected through systematic random sampling across seven primary health centers (Puskesmas) and 17 urban and rural villages. Data were collected using a structured questionnaire and analyzed to determine factors associated with complete nOPV2 immunization. Several factors showed significant associations with nOPV2 dose completion, including fear of adverse events following immunization (AEFI), accessibility of immunization posts and schedules, parental availability, and exposure to negative rumours about immunization. In contrast, parental knowledge about the Polio SIA was not significantly associated with nOPV2 completion among children aged 0–7 years. These findings highlight the importance of strengthening information dissemination, improving service accessibility, and enhancing health promotion strategies to increase community acceptance and ensure successful implementation of immunization programs.